ANALISIS POLICY CONTENT PENATAAN TRANSPORTASI ANGKUTAN UMUM DI KOTA BANDUNG - Arif Moelia Edie (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2019)
This study aims to analyze the policy content of Local Regulation 16/2012. Data are collected through interviews, observation and documentary study. In term of content of policy, the policy has affected the interests of community, transportation operator and the government as regulator. The policy does not offer economic benefits that can be directly accessed, thus community and the operators do not support the implementation. The change envisioned by the policy has large scope, which are not only about the system and infrastructure, but also driving behaviors and mindset about social prestige. Although the Office of transportation is the main site of decision making, there are many programs made politically beyond the formal mechanism. Program implementers consists of Office of Transportation, Office of Roads and Waters, Office of Land Use and Public Works and Office of Local Revenues, thus many overlaps and miss-coordination. The financial resources is insufficiently allocated for the policy. Keywords: Policy Implementation, Public Transportation Arrangement